ANALISIS DIAGRAM WIND ROSE DI BARON TECHNO PARK - Prasetyo, Ridwan Budi (Nozzle : Journal Mechanical Engineering, 2021)
This paper presents the analysis of wind data at KST Baron Techno Park in the form of a wind rose diagram. Wind data analyzed in the 2019 period. The wind data is very important for evaluating wind potential, namely, the production of electricity from wind sources. This is because, KST Baron Techno Park is still experiencing difficulties in obtaining long-term anemometric data and short-term data related to wind speed and wind direction. Even though this is very important for the optimization of the operation and maintenance of the Wind Power Plant (PLTB) which is part of the hybrid electricity system. This is to examine the characteristics of the wind that several times caused damage to the blade until it broke. Making wind rose diagrams using Microsoft Excel. From the analysis, it is known that the wind direction is dominated by the southeast (SE) with a wind speed of 1-4 m/s.